2013
DOI: 10.1097/dcr.0b013e3182788c77
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Preoperative Biopsy in the Management of Solid Presacral Tumors

Abstract: Preoperative biopsy of presacral tumors is safe and highly concordant with postoperative pathology in comparison with imaging. Given the significant differences in therapeutic approach for benign versus malignant solid presacral tumors, as well as the current limitations of imaging, a percutaneous preoperative biopsy should be obtained to guide management decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 22 publications
2
45
1
2
Order By: Relevance
“…The authors have suggested previously that good quality MRI and/or CT images are sufficient to establish the diagnosis and to plan the surgical procedure. Although this view is supported by a number of authors, some have argued that such biopsies compromise safety and risk seeding tumour along the biopsy track; others have argued that a percutaneous preoperative biopsy should be obtained to guide management decisions. Although biopsy is safe if the transrectal approach is avoided, and is concordant with the postoperative pathology findings, it rarely influences management.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have suggested previously that good quality MRI and/or CT images are sufficient to establish the diagnosis and to plan the surgical procedure. Although this view is supported by a number of authors, some have argued that such biopsies compromise safety and risk seeding tumour along the biopsy track; others have argued that a percutaneous preoperative biopsy should be obtained to guide management decisions. Although biopsy is safe if the transrectal approach is avoided, and is concordant with the postoperative pathology findings, it rarely influences management.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, given the limitations of imaging to make a definitive diagnosis, percutaneous biopsy of solid or heterogeneous presacral tumors could be obtained preoperatively to facilitate decision making for the use of neoadjuvant therapies and for optimizing surgical planning. 29 On the other hand, there is the fear that it can lead to contamination or tumor spread. Some authors only recommend a biopsy to be performed if the lesion appears to be unresectable and if a tissue diagnosis is required to guide neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been argued that MRI is sufficient to allow surgical planning and prediction of potential complications [2,16], and a recent study found that the results of preoperative biopsy did not influence management [13]. A recent study by Merchea et al [15], however, has shown that preoperative biopsy is safe and allows optimal management of the tumour. They reported a specificity of 100% in differentiating between benign and malignant disease on preoperative biopsy with a sensitivity of 96% compared with a specificity and sensitivity of 81% and 83% for imaging alone.…”
Section: Discussionmentioning
confidence: 99%